Refining distant metastasis stage in oral squamous cell carcinoma - Xiaodong Sun; Qigen Fang; Junhui Yuan; Xu Zhang; Liyuan Dai; Fei Liu; Lisong Lin; Hui Zhao (World Journal of Surgical Oncology)
Abstract Background This study aimed to investigate the impact of varying distant metastatic burdens on prognosis in oral squamous cell carcinoma (OSCC) and to propose a novel staging system for distant metastasis. Methods We retrospectively enrolled patients with primary stage IVc OSCC at diagnosis or those who developed confirmed distant metastasis within six months after curative treatment. These patients were divided into training and validation cohorts. The prognostic accuracy of the 8th edition AJCC staging system and our proposed staging system was evaluated based on overall survival (OS). Results Among the 586 patients analyzed, 317 were assigned to the training cohort. OS was significantly influenced by the number of metastatic foci and the number of affected anatomic sites, but not by the size of the metastatic foci. Compared to stage IVc1 (defined as ≤ 3 metastatic foci within a single anatomic site), stage IVc2 (4–5 metastatic foci in one site or 2–5 foci across two sites) and stage IVc3 (all other distant metastasis patterns) were associated with hazard ratios of 1.35 (95% CI: 1.10–1.47) and 1.87 (95% CI: 1.51–2.43), respectively. Our proposed model achieved a concordance index of 0.691 and a likelihood ratio of 0.507, demonstrating superior discriminatory ability between patient subgroups and better homogeneity within subgroups compared to the AJCC system. Additionally, the new staging system remained an independent prognostic factor in the validation cohort. Conclusions In primary stage IVc OSCC, the extent of distant metastatic burden significantly affects OS. Our novel staging system offers more precise prognostic stratification than the current AJCC classification. However, further validation through prospective studies is warranted.